Nama Tokoh Sebagai Teks Acuan dalam Penulisan Judul Program Kreativitas Mahasiswa 5 Bidang (Studi Prior Text) - Nivia Putri Ratna Juwita; Atiqa Sabardila; Markhamah (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
This study aims to identify and describe the prior text used as a reference text in writing the title Program Kreatifitas Mahasiswa 5 in the Field of Funding for the 2018 Fiscal Year. This research belongs to qualitative descriptive research that is naturalistic in nature. The data source used in this study is in the form of Program Kreatifitas Mahasiswa Title 5 Fields funded in 2018. The data generated in the form of words and sentences contained in the data source is Title Program Kreatifitas Mahasiswa 5 in Funding Budget Year 2018. Data analysis methods in the form of translational matching methods, abductive inference methods, and the referential equivalent method. Test the validity of the data using theory triangulation. The results of the study found the writing of Program Kreatifitas Mahasiswa Title 5 in Funding for the Fiscal Year 2018 is a transformation or adaptation text that utilizes several names of characters, including: (1) the names of public figures; (2) the name of the hero; (3) the name of an animated or fictional character; and (4) the name of the artist. The findings in this study indicate that the name of the artist as a reference text has a high appeal to attract readers.